Cryptic natural autoantibodies and co-potentiators - Cheng, Hwee Ming; Chamley, Lawrence (Elsevier, 2008)
Natural autoantibodies are normal components of the humoral arm of the immune system found in clinically healthy individuals. There are two subpopulations of natural antibodies, including an overt group of antibodies that are readily detected in unfractionated normal human sera. The other natural antibody subgroup is revealed by physico or biochemical treatment of normal human sera in vitro. Unmasking of this latter cryptic natural autoantibodies (cNA) may occur in vivo by local factors in the tissue environment of disease states. The masking cryptic factors may be immunoglobulin (Ig) or non-Ig in nature. These factors may either be co-inhibitors or co-enhancers of cNA. In the heat-potentiated binding of natural anti-phospholipid antibodies, apolipoprotein H (beta 2-glycoprotein I) appears to act as a co-enhancer. The immuno-relationship between the in vitro and in vivo cNA phenomenon remains to be elucidated.